2003
DOI: 10.1007/s00213-002-1375-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 8-OH-DPAT and WAY-100635 on performance on a time-constrained progressive-ratio schedule

Abstract: The results suggest that 8-OH-DPAT enhanced the activating effect of the reinforcer (the highest dose may also have induced motor debilitation). The finding that the effect of 8-OH-DPAT on a was attenuated by WAY-100635 implicates 5-HT(1A) receptors in this effect. The results are consistent with previous reports that 8-OH-DPAT facilitates feeding and food-reinforced operant responding in rats and suggest that these effects may be brought about by an increase in food motivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
30
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 40 publications
21
30
0
Order By: Relevance
“…Equation 1 was fitted to the overall response rate data from each rat under each treatment condition using an iterative least-squares method (SigmaPlot, Version 8.0), and the estimated values of the parameters β, δ and a were derived; goodness of fit was expressed as r 2 , the proportion of the data variance accounted for by the equation. In agreement with previous findings (Mobini et al 2000;Ho et al 2003;Zhang et al 2005aZhang et al , 2005bBezzina et al 2008aBezzina et al , 2008bRickard et al 2009), examination of the data revealed that in some rats very low response rates were generated under the highest ratios, which did not conform to Equation 1. Therefore the equation was fitted to each rat"s data after exclusion of these low rates using the following operational criterion (Mobini et al 2000).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Equation 1 was fitted to the overall response rate data from each rat under each treatment condition using an iterative least-squares method (SigmaPlot, Version 8.0), and the estimated values of the parameters β, δ and a were derived; goodness of fit was expressed as r 2 , the proportion of the data variance accounted for by the equation. In agreement with previous findings (Mobini et al 2000;Ho et al 2003;Zhang et al 2005aZhang et al , 2005bBezzina et al 2008aBezzina et al , 2008bRickard et al 2009), examination of the data revealed that in some rats very low response rates were generated under the highest ratios, which did not conform to Equation 1. Therefore the equation was fitted to each rat"s data after exclusion of these low rates using the following operational criterion (Mobini et al 2000).…”
Section: Discussionsupporting
confidence: 90%
“…Performance on the progressive-ratio schedule was similar to that seen in many previous studies (Bizo and Killeen 1997;Mobini et al 2000;Ho et al 2003;Kheramin et al 2005;Zhang et al 2005aZhang et al , 2005bBezzina et al 2008aBezzina et al , 2008bKilleen et al 2009;Rickard et al 2009). Overall response rate was bitonically related to ratio size; it increased rapidly to reach a peak, and then declined gradually as the response/reinforcer ratio was progressively increased.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations